PERANAN HUKUM ADAT DI INDONESA PADA ERA GLOBALISASI - Fathur Rohman Brasal (Universitas Muhammadiyah Jember, 2021)
Many people argue that customary law is not a law because it has become a habit factor and done over and over again in a certain tribal area. Customary law has occurred from the old days of the Dutch colonial era, which can be wrong in law both punishment of torture and death law. As in the Borneo area if caught stealing will be in the punishment of torture by local residents, just as in today if there is caught stealing or grab if caught will be in the period when it has become the habit of almost all regions in Indonesia as well as in the area of Papua which if his brother died his finger on the piece indicates the lost brother lost his fingers, and it has been done over and over and has become a habit of the area until now. In today's customary law is still going on in the era of globalization but only in certain areas such as the developed areas of customary law has begun to change has started to follow the era, for example in the sophistication of the era of many crimes are done using sophisticated era such as news that often occurs in Hoax nowadays.